An Ex-Ante Assessment on Poverty and Cash Transfer Benefits in Viet Nam under the Covid-19 Pandemic - Long Thanh Giang; Aiko Kikkawa; Cuong Viet Nguyen (Global Labor Organization (GLO), 2021)
Using household data from the Vietnam Household Living Standard Survey (VHLSS) and the sector-specific growth and remittance inflow projections by Asian Development Bank (ADB), this study first estimated the COVID-19 pandemic on income and poverty status of the Vietnamese households, and then simulated the impact of cash transfer programs by the government of Vietnam on the income and poverty status of households. Our simulations suggest that COVID-19 leads to substantial reduction in household's per-capita income, and results in additional 1.7 million poor people. The cash transfers would be pro-poor and helps bring about 1.2 million people out of poverty. The transfers would be particularly pro-poor for ethnic minority and rural persons and those working in severely affected economic sectors. Based on the findings, we discussed various policies to implement appropriate measures to help households cope with adverse economic impact of COVID-19.
Keywords: 330; COVID-19; poverty; income; microsimulation; Vietnam